The Impact of Bureaucracy Simplification: The Experience of Lumajang District - Aksanul Inam; Supranoto; Hari Karyadi (Jurnal Ilmu Pemerintahan : Kajian Ilmu Pemerintahan dan Politik Daerah, 2025)
One of the efforts to make bureaucracy more effective and efficient is by simplifying the bureaucracy. This effort to simplify the bureaucracy was conveyed by Indonesian President Joko Widodo during his inauguration as the President of Indonesia for the second term on October 20, 2019. The simplification of bureaucracy involves reducing the bureaucratic span from 5 (five) levels to just 2 (two) levels. The Lumajang Regency Government, as one of the government institutions, has also implemented this bureaucratic simplification. There are 3 (three) sequential stages carried out, namely Simplification of Organizational Structure, Position Equalization, and Work System Adjustment. This research aims to describe the process, consistency, and impact of the implementation of the bureaucratic simplification policy within the Lumajang Regency Government. The theory used is the public policy implementation theory by Paul A. Sabatier and Daniel A. Mazmanian. This research employs a qualitative descriptive method with data collection techniques through interviews and documentation. The results of the study show that impact of implementing the bureaucratic simplification were found between the objectives and their operationalization, for example, the issuance of Ministerial Regulation PAN and RB Number 1 of 2023 concerning Functional Positions, which accommodates the conversion of SKP (employee performance targets) values into credit scores. This has led to functional officials no longer being professional in their fields. Regarding the impact of policy implementation, one of the negative impacts is that some functional officials cannot receive functional allowances in accordance with their functional positions because these positions should not be at the Regional Government level.